Treating and controlling digital dermatitis in dairy cattle. Issue 10 (17th December 2020) - Bell, Nick; Vanhoudt, Arne
Abstract : Background: Digital dermatitis (DD) is one of the main causes of lameness in dairy cattle, and is prevalent in most dairy herds worldwide and is of major welfare and economic significance. Aim of the article: This article focuses on current concepts of DD treatment and control strategies, but will not go into detail about most concepts relating to prevention – namely biosecurity, improving foot hygiene, nutrition and genetics. The article includes concepts related to disease screening, treatment at both an individual cow level and with footbaths, and the control of DD through foot disinfection using footbaths. Readers are referred to other detailed reviews where appropriate, such as Plummer and Krull (2017) and Orsel and others (2018).